Toward true health care reform: More care, less insurance - Marshall Auerback; L. Randall Wray (Levy Economics Institute of Bard College, 2010)
The United States has the most expensive health care system in the world, yet its system produces inferior outcomes relative to those in other countries. This brief examines the health care reform debate and argues that the basic structure of the health care system is unlikely to change, because reform measures actually promote the status quo. The authors believe that the fundamental problem facing the US health care system is the unhealthy lifestyle of many Americans. They prefer to see a reduced role for private insurers and an increased role for government funding, along with greater public discussion of environmental and lifestyle factors. A Medicare buy-in (public option) for people under 65 would provide more cost control (by competing with private insurance), help to solve the problem of treatment denial based on preexisting conditions, expand the risk pool of patients, and enhance the global competitiveness of US corporations - thus bringing the US health care system closer to the ideal low-cost, universal (single-payer) insurance plan.
Keywords: 330; Gesundheitsreform; Gesundheitswesen; Gesundheitsfinanzierung; USA